Mitochondrial Bioenergetics Profile With Different Mechanistic Target of Rapamycin Complexes (mTORC1/mTORC2) Inhibitors in Pancreatic Beta-Cell Lines (Beta-TC-6). (7th June 2021) - Soliman, Ghada; He, Ye
Abstract: Objectives: We investigated the impact of mTOR complexes inhibition with RapaLink-1, a third-generation bivalent mTORC1/mTORC2 inhibitor that links rapamycin with a mTOR-kinase inhibitor, or Torin-2 (ATP-competitive) on mitochondrial dynamics, bioenergetics, and extracellular flux. Methods: We used insulin-secreting, glucose-responsive pancreatic beta cells derived from transgenic mice expressing SV40 (Beta-TC-6 cells, ATCC-11506). Cells were treated for 24 hours with either: RapaLink; Torin-2; rapamycin; metformin; a combination of metformin and RapaLink, or Torin-2; compared to vehicle control. Bioenergetic dynamics and cellular metabolism were quantified using MitoStress Test XF24 (Agilent, Seahorse). The real-time, live-cell approach simultaneously measures oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) to determine cellular respiration and metabolism. Statistical significance was assessed by ANOVA followed by an unpaired t-test. Results: Rapalink-1 and Torin-2 incubation decreased basal OCR compared to rapamycin alone or vehicle control (189.58 ± 48.58, 116.85 ± 26.55 versus 405.01 ± 21.57, 444.19 ± 58.59, p < 0.01) in Beta TC-6 pancreatic cell lines. ATP production was also significantly reduced in RapaLink-1 (122.23 ± 33.19), Torin-2 (72.37 ± 17.33) treated cells, compared to rapamycin (250.45 ± 9.41) and vehicle control (274.23 ± 38.17), p < 0.01. Similarly, proton leak decreased in RapaLink-1 (67.34 ± 15.40) and Torin-2 (44.48 ± 9.23) treated beta cells, compared to rapamycin (154.56 ± 12.53) or control (169.96 ± 20.52), p < 0.01. However, non-mitochondrial oxygen consumption was not statistically different between RapaLink (67.17 ± 3.52) Torin-2 (55.93 ± 8.76) or rapamycin (80.01 ± 4.36), but was less than the control group (108.80 ± 7.19), p = 0.006. Conclusions: The combination of mTORC1 and mTORC2 inhibition by RapaLink-1 or Torin-2 decreased mitochondrial respiration compared to rapamycin treatment. Decreased OCR suggests reduced initial energy requirements, while decreased ATP production indicates decreased energy demands. Third-generation mTOR inhibitors may alter the mitochondrial dynamics and reveal a mitochondrial bioenergetics profile that could be targeted to reduce mitochondrial stress. Funding Sources: City University of New York, GC Advanced Science Research Center Seed Grant Award